Blood Utilization for Elective Orthopaedic Surgeries at Maharat Nakhon Ratchasima Hospital - Wong-Aek, MD, Jumpotpong; Lewsirirat, MD, Supphamard; Piyapromdee, MD, Urawit (Journal of Southeast Asian Orthopaedics, 2022)
Background: Elective orthopaedic surgeries incur unavoidable blood loss and may need blood replacement. Over preoperative blood requesting results in unnecessary crossmatching. Aim: To audit blood ordering and utilization in elective orthopaedic surgeries at Maharat Nakhon Ratchasima hospital for a one year period and recommend guidelines for blood orders. Materials and Methods: A 1 year retrospective analysis of patients who underwent elective orthopaedic surgeries. Patients’ age, sex, type of operative procedure, pre- and postoperative hematocrit (Hct) levels, number of units crossmatched, transfusion, crossmatch to transfusion ratio (C:T), transfusion probability, transfusion indices, and the actual and predicted fall in Hct were reviewed and a blood ordering schedule proposed based on a surgical blood ordering equation. Results: 1,417 patients underwent 25 kinds of elective orthopaedic procedures. 1987 units of blood were cross-matched, but only 296 units were transfused. Transfusions were never used in seven procedures. All of the 25 procedures had C:T >2.0. Nineteen of the 25 procedures had transfusion probabilities of <30 percent. Twenty from 25 procedures had a low transfusion index (Ti<0.5). The results demonstrated that the majority of preoperative blood orders were unnecessary. Seven of the 25 elective surgical procedures did not require preoperative blood orders. This study recommends blood ordering guidelines based on patients and surgical variables which leads to the maximum utilization of blood.